(3GdeYLe GdUZjQs - (3SdjeGf Hf CMeO Hf CjhH Hf eWjQ GddNej GdTGej, CHh GdbGSe, J (B360 (3g` s ((3eMeO Hf CHj fUQ Hf eMeO Hf CMeO Hf YeQ GdbGSGfi s)
(3ChdgG (B:s
(3jHJOF HMOjK (B:" (3ef bGd YfO fheg (B: (3Gddge Efi ahVJ CeQi Edjc hCSdeJ faSi Edjc EdN s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B121s
Keywords: (3GdMOjK h GdeUWdMs